1997
DOI: 10.1097/00005373-199709000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Polytrauma

Abstract: Although the short-term impact of injuries is extensive, the long-term outcomes are satisfactory. Severe injuries sustained during childhood do not lead to a diminished quality of life during adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Of these, all except two (Janssens et al 2009; van der Sluis et al 1997) found reductions in overall HRQOL in their injured samples at at least their initial evaluation point. Additionally, Soori and Abachizadeh (2008) found significant associations between overall HRQOL and having experienced a traumatic injury in the previous year.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Of these, all except two (Janssens et al 2009; van der Sluis et al 1997) found reductions in overall HRQOL in their injured samples at at least their initial evaluation point. Additionally, Soori and Abachizadeh (2008) found significant associations between overall HRQOL and having experienced a traumatic injury in the previous year.…”
Section: Resultsmentioning
confidence: 98%
“…Six studies reported on overall HRQOL in children and adolescents after traumatic injury (Holbrook et al 2007; Janssens et al 2009; Landolt et al 2009b; Sturms et al 2002; van der Sluis et al 1997; Vollrath and Landolt 2005). Of these, all except two (Janssens et al 2009; van der Sluis et al 1997) found reductions in overall HRQOL in their injured samples at at least their initial evaluation point.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations